155k views
1 vote
Simplify the expression. Someone help please...

Simplify the expression. Someone help please...-example-1
User F Blanchet
by
4.9k points

1 Answer

3 votes

Answer:


\sqrt[4]{768x^8y^5} = 4x^2y \sqrt[4]{3y}

Explanation:

Given


\sqrt[4]{768x^8y^5}

Required

Simplify

We have:


\sqrt[4]{768x^8y^5}

Expand 768


\sqrt[4]{768x^8y^5} = \sqrt[4]{256 * 3 * x^8y^5}

Split


\sqrt[4]{768x^8y^5} = \sqrt[4]{256} * \sqrt[4]{3 * x^8y^5}


\sqrt[4]{256} = 4

So, we have:


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3 * x^8y^5}

Expand y^5


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3 * x^8*y *y^4}

Rewrite as:


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3*y * x^8 *y^4}


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3y * x^8 *y^4}

Split


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3y} * \sqrt[4]{x^8 *y^4}

Apply the following law of indices


\sqrt[a]{b} = b^(1)/(a)


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3y} * (x^8 *y^4)^(1)/(4)

Expand


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3y} * x^{8*(1)/(4)} *y^{4*(1)/(4)}


\sqrt[4]{768x^8y^5} = 4* \sqrt[4]{3y} * x^2y

Rewrite as:


\sqrt[4]{768x^8y^5} = 4* x^2y* \sqrt[4]{3y}


\sqrt[4]{768x^8y^5} = 4x^2y \sqrt[4]{3y}

User Bo Fjord Jensen
by
4.7k points